Comparative effectiveness of tenofovir versus entecavir in patients with hepatitis B virus-related cirrhosis in Taiwan: a retrospective cohort study - Huang, Yu-Han; Shen, Chuan-Wei; Chen, Chung-Yu; Bair, Ming-Jong (Frontiers in Pharmacology, 2023)
Background: Tenofovir and entecavir demonstrated substantial effectiveness in the reversion of fibrosis and reversed cirrhosis in patients with hepatitis B virus (HBV)related cirrhosis. However, there has not been a definitive conclusion regarding the association between entecavir and tenofovir on the risk of cirrhosis-related complications. Therefore, this study aimed to investigate the comparative effectiveness between tenofovir and entecavir in HBV-related cirrhosis patients.This was a retrospective study using Taiwan's Health Insurance Research Database. We enrolled newly diagnosed HBV-related cirrhosis who initiating entecavir and tenofovir between 2011 and 2019. Treatment groups were determined by the initial HBV antiviral medication prescribed. The primary composite outcome was development of hepatocellular carcinoma, death from any causes, and liver transplantation. Secondary outcome included all individual components of the primary outcome. Incidence rate was calculated in each outcome for both treatment groups by Fine-Gray subdistribution hazards models. Propensity score adjustment was utilized to balance treatment groups.Results: A total of 7316 propensity score-matched treatment naïve patients and 3524 propensity score-matched treatment experienced patients were included. Within treatment naïve patients, patients receiving tenofovir showed significantly lower hazards of developing composite outcome (HR, 0.79; p <0.0001), hepatocellular carcinoma (HR, 0.86; p=0.027), mortality (HR, 0.75; p < 0.0001), and liver transplantation (HR, 0.70; p = 0.0189) than those receiving entecavir. As for treatment experienced patients, tenofovir was associated with a significantly lower risk of composite outcome (HR, 0.82; p = 0.0033), hepatocellular carcinoma (HR, 0.60; p < 0.0001) but not achieving significantly different risk of all-cause mortality (HR, 0.93; p = 0.3374) or liver transplantation (HR, 1.17; p = 0.5112) compared to entecavir.Conclusions: Tenofovir presented significantly lower incidence of cirrhosis-related complications compared with entecavir in patients with hepatitis B virus-related cirrhosis. However, no statistical significant difference in death and liver transplantation was seen in treatment experienced patients.